Innovative Oil from STIFA Pelita Mas for Glycemic Control and Tissue Regeneration in Diabetic Rats - Joni Tandi; Muthmainah Tuldjanah; Tien Wahyu Handayani (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Diabetes mellitus is a significant global health problem with increasing prevalence in Indonesia. Conventional management of diabetes mellitus is often accompanied by side effects and high costs, prompting the search for alternatives based on natural ingredients. STIFA Pelita Mas Herbal Oil is an innovative formulation that combines various efficacious natural ingredients, but its effectiveness on histopathological changes in pancreatic and kidney tissues due to diabetes has not been comprehensively explored. This study aims to evaluate the effectiveness and mechanism of action of STIFA Pelita Mas Herbal Oil on reducing blood glucose levels, repairing pancreatic tissue damage, and kidneys in a streptozotocin-induced rat model. Methods: This study used a quantitative approach with an experimental design on 30 male white rats (Rattus norvegicus) divided into 6 treatment groups. STIFA Pelita Mas Herbal Oil is made by combining simplicia (Shallots, Garlic, Ginger, Curcuma zanthorrhiza, Lemongrass red, and Piper ornatum leaves) with various oils (VCO, eucalyptus oil, citronella oil, olive oil, and cinnamomum cullilawan). Diabetes was induced using streptozotocin (40 mg/kg BW) intraperitoneally. The parameters measured included blood glucose levels and histopathological changes in the kidneys and pancreas with Hematoxylin-Eosin staining. Data were analyzed using One Way ANOVA followed by the LSD or Kruskal-Wallis test. Result: The results showed that all three herbal oil formulas were able to lower blood glucose levels, with formula 1 and formula 3 showing comparable effectiveness to glibenclamide on day 28. In histopathological observations of the kidneys, formula 3 showed the best effectiveness in repairing damage to renal tubule and glomerular cells with a damage score of 0, equivalent to normal controls. Similarly, in histopathological observations of the pancreas, formula 3 showed the highest effectiveness in repairing damage to pancreatic beta cells with a damage score of 0.2, not significantly different from normal and positive controls. Conclusion: Stifa Pelita Mas herbal oil, especially formula 3, has the potential as an effective antidiabetic agent in lowering blood glucose levels and repairing tissue damage in the kidneys and pancreas due to diabetes. Future research should focus on dose variations to see at what dose this oil is effective.